2017
DOI: 10.1097/jac.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health Care and Cervical Cancer Mortality Rates in Brazil

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
0
17
0
9
Order By: Relevance
“…Ovarian cancer is the second most common cancer and main cause of death with gynecological tumors worldwide (Qin et al, 2013;Zhu and Sun, 2017). Moreover, cervical cancer is the third most frequent neoplasm among women worldwide (Rocha et al, 2017). In 2017, a study showed that ovarian cancer (47%) followed by cervical cancer (29%) are the most common gynecological malignancy among Pakistan women (Manzoor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is the second most common cancer and main cause of death with gynecological tumors worldwide (Qin et al, 2013;Zhu and Sun, 2017). Moreover, cervical cancer is the third most frequent neoplasm among women worldwide (Rocha et al, 2017). In 2017, a study showed that ovarian cancer (47%) followed by cervical cancer (29%) are the most common gynecological malignancy among Pakistan women (Manzoor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] The mortality rate stability in the post-PNAISM period detected in the present study may be regarded as an expected result, given the cancer progression time from early detection to the time of death with respect to breast 28 and cervical 29 cancers as well as an improvement in the lling out of forms and in the quality of information of the information systems concerning the causes of death. [28][29][30] Still, the stability of the cancer mortality rates may be viewed as a warning for the type of unorganized screening performed in Brazil, with breast and cervical cancers at the forefront in women's health. 31 There was no reduction in deaths from respiratory diseases, a nding also shown in the results of Schmitt et al 8 The implementation success of other public policies, such as that of smoking, 32 could have changed the outcome.…”
Section: Discussionmentioning
confidence: 61%
“…Cuts in health care spending have come on top of old challenges associated with inequity in the distribution of the medical work force. The potential excess deaths projected in our research may be associated with other health problems, such as additional costs for emergency services (30,31) and an increase in disabilityadjusted life years (32).…”
Section: Discussionmentioning
confidence: 90%